Theoretical issues of information sources for the formation of separate methods of investigating criminal offenses - A. Ye. Holubov (Bulletin of Kharkiv National University of Internal Affairs)
The subject of the study is to provide a detailed description of the sources of formation of certain forensic methods of investigating criminal offenses. The purpose of the article is to clarify the concept, content, meaning and system of such sources.